A new eriophyoid mite species (Acari: Eriophyoidea) on Picea abies (Pinaceae) - Lewandowski, Mariusz (Zootaxa, 2006)
A new eriophyoid species, Calepitrimerus lutocinus n. sp., a vagrant on Picea abies in Poland, is described. It is the first Calepitrimerus species reported from Picea plants.